The Effect of Young People Not in Employment, Education or Training, on Poverty Rate in European Union - Ionut Jianu (Journal of Eastern Europe Research in Business and Economics, 2019)
This paper aims to estimate the effect of young people who are not in employment, education or training (neets rate) on the people at risk of poverty rate in the European Union. Statistical data covering the 2010-2016 period for all EU-28 Member States have been used. Regarding the methodology, the study was performed by using Panel Estimated Generalized Least Squares method, weighted by Period SUR option. The effect of neets rate on poverty rate proved to be positive and statistically significant in European Union, since this indicator includes two main areas which are extremely relevant for poverty dimension. Firstly, young unemployment rate was one of the main channels through which the financial crisis has affected the population income. Secondly, it accounts for the educational system coverage and its skills deficiencies.
Keywords: I24; I30; I32; J21; 330; poverty; education; employment; social; panel